Application of metal foams to high temperature PEM fuel cells. (28th September 2016) - Tseng, Chung-Jen; Heush, Ying-Jui; Chiang, Chien-Jui; Lee, Yi-Hsuan; Lee, Kan-Rong
Abstract: The performance of a high temperature proton exchange membrane fuel cell (HT-PEMFC) with metal foam as the flow field is investigated. The HT-PEMFC is assembled using commercial membrane electrode assembly, Advent TPS ® HT PEM MEA. In addition to metal foam flow field, conventional graphite serpentine flow is also used to assemble a single cell using the same MEA for comparison. Effects of operating temperature, stoichiometry, gas preheating temperature, and humidification on cell performance are investigated. AC impedance analysis is also used to study the changes in various resistances and electrochemical mechanisms inside the cell. Results show that metal foam flow field, having high gas permeability, improves gas convection and diffusion, and increases the chance of reaction with the catalysts. The porous structure of metal foam can effectively reduce the contact resistance between the flow plate and carbon paper. The current density at 0.6 V of metal foam fuel cell is approximately 20% higher than conventional graphite serpentine flow channel fuel cell. Increasing the operating temperature, stoichiometry, or humidification, improves the cell performance. Initial 300 h operation test shows the cell is relatively stable. Highlights: Metal foam flow field is applied to HT-PEM fuel cell. Metal foam cell's performance is 20% better than conventional cell. Low air stoichiometry suffices for stable operation. Effects of operating parameters are investigated.